2014
DOI: 10.1007/s00392-014-0672-8
|View full text |Cite
|
Sign up to set email alerts
|

Not left ventricular lead position, but the extent of immediate asynchrony reduction predicts long-term response to cardiac resynchronization therapy

Abstract: Cardiac resynchronization therapy (CRT) is an effective treatment for a large subgroup of chronic heart failure patients. Various attempts to improve the high non-responder rate of 30 % by preoperative asynchrony assessment have failed. We hypothesized that superior response to CRT is correlated with greater acute reduction of asynchrony and that a concordant left ventricular (LV) lead is beneficial compared to a discordant lead. Hundred and eight consecutive CRT patients from our center were prospectively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…In fact, pooled data have demonstrated that one-third of patients undergoing CRT fail to experience symptomatic benefit, with only 60% exhibiting a favorable echocardiographic response 12,13 and approximately 20% being considered super-responders. 12 Comparable echocardiographic responder rates (decrease in LVESV $15%) of 63% and 60% were reported at 6-month follow-up by Poller et al 15 and Shetty et al, 16 respectively. In the present study, the rates of clinical responders with reverse remodeling were almost 80%, and the majority of responders were classified as super-responders.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, pooled data have demonstrated that one-third of patients undergoing CRT fail to experience symptomatic benefit, with only 60% exhibiting a favorable echocardiographic response 12,13 and approximately 20% being considered super-responders. 12 Comparable echocardiographic responder rates (decrease in LVESV $15%) of 63% and 60% were reported at 6-month follow-up by Poller et al 15 and Shetty et al, 16 respectively. In the present study, the rates of clinical responders with reverse remodeling were almost 80%, and the majority of responders were classified as super-responders.…”
Section: Discussionmentioning
confidence: 88%
“…Of 3084 unique citations identified, a total of nine publications from eight unique studies met the selection criteria for this analysis (Figure 1). [6][7][8]11,13,16,17,20,21 Two publications from the Targeted Left Ventricular Lead Placement to Guide Cardiac Resynchronization (TARGET) study were included, but considered as only one study for analyses. 7,13 Of the nine publications, four were secondary analyses of data from RCTs, four were prospective observational studies, and one combined patients from a RCT and a prospective observational study.…”
Section: Resultsmentioning
confidence: 99%
“…6 In a third study, SD for absolute change in LVEF was not provided and thus the SD at baseline and follow-up were assumed to be the same and the correlation was conservatively estimated at 0.5. 17 For LVESV, the mean (SD) of the relative change, expressed as a percentage, from baseline was reported. For two studies, the mean relative change in LVESV was estimated using the reported means at baseline and follow-up and the SD was calculated assuming a conservative correlation between baseline and follow-up of 0.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigations attempted to identify super-responders focusing on various echocardiographic parameters of reverse remodeling. Yu et al [11], Ypenburg [6] and Poller [12] defined super-responder by an improvement in left ventricular end-systolic volume (LVESV), although different cut-offs were selected [6,11]. Another study group used vectorcardiography parameters to assess response to CRT [13].…”
Section: Introductionmentioning
confidence: 99%